S-layer and cytoplasmic membrane – exceptions from the typical archaeal cell wall with a focus on double membranes - Klingl, Andreas (Frontiers in Microbiology, 2014)
The common idea of typical cell wall architecture in archaea consists of a pseudo-crystalline proteinaceous surface layer (S-layer), situated upon the cytoplasmic membrane. This is true for the majority of described archaea, hitherto. Within the crenarchaea, the S-layer often represents the only cell wall component, but there are various exceptions from this wall architecture. Beside (glycosylated) S-layers in (hyper)thermophilic cren- and euryarchaea as well as halophilic archaea, one can find a great variety of other cell wall structures like proteoglycan-like S-layers (Halobacteria), glutaminylglycan (Natronococci), methanochondroitin (Methanosarcina) or double layered cell walls with pseudomurein (Methanothermus and Methanopyrus). The presence of an outermost cellular membrane in the crenarchaeal species Ignicoccus hospitalis already gave indications for an outer membrane similar to Gram-negative bacteria. Although there is just limited data concerning their biochemistry and ultrastructure, recent studies on the euryarchaeal methanogen Methanomassiliicoccus luminyensis, cells of the ARMAN group, and the SM1 euryarchaeon delivered further examples for this exceptional cell envelope type consisting of two membranes.